The Role of International Criminal Court in Prosecuting Crimes against Humanity - Hudjolly Hudjolly (Westscience Press, 2023)
Crimes against humanity are grave offenses that shock the conscience of humanity, and demand a strong international response. The International Criminal Court (ICC), established in 2002, plays an important role in prosecuting individuals responsible for such heinous crimes, including genocide, war crimes, and crimes against humanity. This research explores the role of the ICC in prosecuting crimes against humanity in Indonesia, a country with a complex history of human rights violations. Through a qualitative research design, including case studies, legal analysis, and content analysis, it assesses the effectiveness of the ICC's interventions, analyzes the international legal framework guiding its actions, explores the challenges faced, and evaluates Indonesia's cooperation with the court. The findings show a mixed record of effectiveness, with challenges in evidence collection, witness protection, and limited cooperation hampering some cases. Despite these obstacles, the ICC's involvement has shed light on past atrocities and provided an opportunity for victims to seek justice. The study concludes with recommendations to improve the effectiveness of the ICC in addressing crimes against humanity in Indonesia and underscores the importance of continued efforts to promote accountability and justice on a global scale.